Improving the Knowledge and Attitudes of Premenopausal Women in Facing Physical Changes during Menopause through Audiovisual Media Health Education - Susanti, Nanik; Hidayati, Ulfa Nur; Winarsih, Lilik; Wardani, Arti (Jurnal Kesmas Prima Indonesia, 2025)
Lack of understanding about premenopause can affect women's attitude and readiness to face it. Education through audiovisual media increases knowledge and forms positive attitudes more effectively. This study assessed the effect of audiovisual education on the knowledge and attitudes of premenopausal women in dealing with physical changes during menopause. The research design used was pre-experimental with a one-group pretest-posttest design. The research was conducted at Kauman Husada Clinic in Malang. The research was conducted in November - December 2024. The study population was all premenopausal women aged 40-50, with 50 people obtained by a total sampling technique. The dependent variables of this study are knowledge and attitude. The independent variable is health education with audiovisual media. This study's intervention was providing health education through audiovisual media. Data was collected directly by giving knowledge and attitude questionnaires before and after the intervention. The stages of data analysis began with calculating the frequency distribution of knowledge and attitudes before and after the intervention, using the t-Wilcoxon test. The results showed differences in respondents' knowledge before and after audiovisual media education (p = <0.001). There is a difference in the attitude of respondents before and after being given audiovisual media education (p = <0.001). The conclusion is that providing education using audiovisual media significantly affects the increase in knowledge and attitudes of respondents.